Propionate Ameliorates Staphylococcus aureus Skin Infection by Attenuating Bacterial Growth - Jeong, Soyoung; Kim, Hyun Young; Kim, A Reum; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Microbiology, 2019)
Staphylococcus aureus causes various diseases including skin and soft tissue infections, pneumonia, gastroenteritis, and sepsis. Antibiotic-resistant S. aureus such as methicillin-resistant S. aureus (MRSA) and multidrug-resistant S. aureus is a serious threat in healthcare-associated settings and in the communities. In this study, we investigated the effects of short-chain fatty acids, metabolites produced by commensal bacteria, on the growth of S. aureus both in vitro and in vivo. Sodium propionate (NaP) most potently inhibited the growth of MRSA and multidrug-resistant clinical isolates. Of note, only NaP, but not sodium acetate (NaA) or sodium butyrate (NaB), ameliorated MRSA skin infection, significantly lowering bacterial load, excessive cytokine production, and the size and weight of abscesses approximately by twofold. In addition, interestingly, S. aureus deficient of lipoteichoic acids (LTA) or wall teichoic acids (WTA), which are important in bacterial physiology and antimicrobial susceptibility, was more susceptible to NaP than the wild-type. Furthermore, S. aureus deficient of D-alanine motifs common in LTA and WTA was more susceptible to NaP, its growth being almost completely inhibited. Concordantly, MRSA treated with an inhibitor of D-alanylation on LTA and WTA was more susceptible to NaP, and co-treatment of NaP and a D-alanylation inhibitor further decreased the pathology of MRSA skin infection. Collectively, these results demonstrate that NaP ameliorates MRSA skin infection by attenuating the growth of S. aureus, and suggest an alternative combination treatment strategy against S. aureus infection.